Implementasi Resource Based Learning (RBL) dalam Pembelajaran Sejarah Untuk Meningkatkan Kemampuan Historical Thinking Siswa di MAN 1 Padangsidimpuan - Purba, Nurcintama (LPTK IAIN Kediri, 2022)
This article aims to analyze the implementation of the Resource Based Learning (RBL) learning model to improve students' historical thinking skills in learning history. This research is a class action research (CAR) which was carried out in two cycles. Each cycle consists of 2 meetings which consist of planning, implementing actions, observing, and reflecting. The research subjects were 36 students of class XII MIA 1 MAN 1 Padangsidimpuan. Data collection techniques using interviews, observation, and HOTS-based tests. Data analysis used descriptive qualitative and quantitative analysis. The results of the research on the ability to think historically in cycle 1 obtained an average score of 73.50. While in cycle 2 it increased to 86.80. From the results of the analysis, it can be seen if students can master the five aspects of historical thinking ability indicators which include: (1) chronological thinking, (2) historical understanding, (3) historical analysis and interpretation, (4) historical research abilities, (5) issue analysis history and decision making. Based on these results, it shows that the Implementation of Resource Based Learning (RBL) can improve the ability of Historical thinking (historical thinking).